The Effect of a Dog Assisted Activity Programme on Elementary Students' Self-Esteem - George Kleftaras and Evangelos Diamantakos (Professor Despina Sapountzi-Krepia, 2024)
The Effect of a Dog Assisted Activity Programme on Elementary Students' Self-Esteem